Direct investigation on high temperature tensile and creep behavior at different regions of directional solidified cast turbine blades. (September 2019) - Wang, X.M.; Hui, Y.Z.; Hou, Y.Y.; Yu, Z.Y.; Li, L.; Yue, Z.F.; Deng, C.H.
Highlights: The specimens were directly achieved from a real DS cast cooled blade. The mechanical properties of specimens from the tenon tooth part are much better than those of the body part. Numerical simulation based on quantitative analysis of microstructures explains the test results. Volume fraction and shape of the γ′ particles are influencing factors for their mechanical performances. Abstract: The mechanical differences between different regions of the directional solidified (DS) blade have been experimentally studied by directly getting specimens from a real DS cast cooled blade. Tensile deformation experiments and creep tests were performed, as well as quantitative microstructure analysis. Results show that the mechanical behaviors, especially the creep properties, of the real DS blade material are worse than those of the standard values obtained from bulk material. The mechanical properties of the tenon tooth are much better than those of the body part of the DS blade. Although visual inspection does not find obvious differences between the microstructures in the body part and the tenon tooth part, quantitative analysis shows that volume fraction, area and shape of the γ′ phase particles are slightly different in tenon tooth part and body part. Finite element models are build based on the quantitative data. Numerical analysis shows that larger volume fraction and small length/width ratio of γ′ phase lead to better tensile and creep behavior of the Nickel-based superalloy at high temperature, which explains the experimental results. In addition, these quantitative differences seem have no influence on their creep fracture mechanisms. The variation of the mechanical properties among different locations of DS turbine blades, as well as the property differences from the standard values of the material, should be paid attention in the design and application of the turbine blade.